2018
DOI: 10.1177/1350650118784728
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication in hot die forging processes

Abstract: This article presents selected aspects of lubricant application, as well as lubrication methods and devices in the context of forging tool durability and accessories used in die forging processes at elevated temperatures. The properties and applications of the currently used lubricating and cooling agents in selected industrial forging processes were analyzed. The authors’ original studies on the influence of lubricant application, dose size, time and feed direction as well as other factors affecting tribologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In the event of a downtime or technological break, the tools are reheated and the temperature of the tools is measured with a pyrometer before the process is started again. In the industrial forging process for lubrication, a fully automatic cooling and lubricating device developed by the authors was used, which was demonstrated in several studies [34][35][36]. Such devices ensure stable and repeatable lubrication conditions.…”
Section: Analysis Of Industrial Forging Processmentioning
confidence: 99%
“…In the event of a downtime or technological break, the tools are reheated and the temperature of the tools is measured with a pyrometer before the process is started again. In the industrial forging process for lubrication, a fully automatic cooling and lubricating device developed by the authors was used, which was demonstrated in several studies [34][35][36]. Such devices ensure stable and repeatable lubrication conditions.…”
Section: Analysis Of Industrial Forging Processmentioning
confidence: 99%
“…Distance between preforming die and workpiece equation: C = 308.7-1.706 D − 2.694 L − 0.491 F + 0.01118 D 2 + 0.00612 L 2 + 0.00780 F 2 + 0.00450 DL − 0.00525 DF + 0.00330 LF (7) The variance analysis of the distance between the preforming die and the workpiece is shown in Table 4.…”
Section: Optimized Die Of the Cdz Of Damping Wallsmentioning
confidence: 99%
“…The molding equipment in the hot forging process will be due to friction and wear, thermal fatigue, plastic deformation and brittle cracks of the mold [1]. If the forging die is deformed, its surface combination and density will change [7][8][9]. The pressure per unit area and the friction of the contact surface, the hardness of the material and the quality of the forging will all affect the mechanical load of the forging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an intensive search is currently taking place to find new technological solutions dedicated to specific forging applications to provide optimal tribological conditions with relatively low financial outlays, while being reliable and easy to implement in die forging shops. For example, in [ 29 ], the authors reviewed modern commercial lubrication systems and presented their proprietary low-cost lubricating and cooling device, the use of which resulted in the reduced forging tool wear. In [ 30 ], the authors developed a lubricating device equipped with a peristaltic pump, which ensured the delivery of a constant dose of lubricant in the front wheel forging process.…”
Section: Introductionmentioning
confidence: 99%